The effect of stocking density on growth in the gilthead sea-bream, Sparus aurata (L.) - Canario, Adelino V. M. (2014)
The effect of stocking density on growth and size variability in gilthean sea-bream, Sprus aurata (L.) was tested by growing juveniles at densities of 0,35 kg m3, 1,3 kg m3 and 3,2 kg m3.